(632) Manpower Planning Model On The Computer نموذج تخطيط القوى العاملة على اجهزة الكمبيوتر - A. Mongy, Mohamed; M. Elewa, Aida (INP, 2024)
This study deals with importance of manpower and some short-term challenges of it. Then, it mentions long – term objectives , role of industrialization and utilizing expertise. Thus, it concludes by clarifying that manpower planning must be an integral part of socio-economic development strategies, focusing on both immediate and long-term solutions to train and prepare the workforce, ensuring they meet the demands of various sectors effectively.